The Role of Behavioral Formality and Informality in the Enactment of Bureaucratic Versus Organic Organizations - Morand, David A. (Academy of Management Review, 1995)
David A. Morand, The Role of Behavioral Formality and Informality in the Enactment of Bureaucratic versus Organic Organizations, The Academy of Management Review, Vol. 20, No. 4 (Oct., 1995), pp. 831-872